2018
DOI: 10.1093/cid/ciy694
|View full text |Cite|
|
Sign up to set email alerts
|

China–United States Research Collaborations in Antimicrobial Resistance

Abstract: A strong synergy can result from China-US antimicrobial resistance (AMR) collaborations given similarities and differences between their respective healthcare systems and research infrastructures. The Antibacterial Resistance Leadership Group has employed a model of realistic growth, starting with a feasible, relatively low-resource observational study in a critical priority pathogen. This and other observational studies will provide vital scientific information required for the rational design of future inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Also, a recent study demonstrated that China leads in terms of the numbers of worldwide reports made on mcr genes (4,917 strains identified in mcr-1 gene, and 274 strains identified in a variant mcr genes) (Elbediwi et al, 2019). The fact that more Chinese students and academics are collaborating with researchers from Western developed countries also contributes to China's growth (Akanwa, 2015;Van Duin et al, 2018). As has been pointed out by other studies (Ramos-Rincón et al, 2019;González-Alcaide et al, 2020), China's emergence in scientific production is remarkable and has advanced by leaps and bounds in recent years (Bornmann et al, 2015), including the area of pharmacology/pharmacy (Ding et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent study demonstrated that China leads in terms of the numbers of worldwide reports made on mcr genes (4,917 strains identified in mcr-1 gene, and 274 strains identified in a variant mcr genes) (Elbediwi et al, 2019). The fact that more Chinese students and academics are collaborating with researchers from Western developed countries also contributes to China's growth (Akanwa, 2015;Van Duin et al, 2018). As has been pointed out by other studies (Ramos-Rincón et al, 2019;González-Alcaide et al, 2020), China's emergence in scientific production is remarkable and has advanced by leaps and bounds in recent years (Bornmann et al, 2015), including the area of pharmacology/pharmacy (Ding et al, 2013).…”
Section: Discussionmentioning
confidence: 99%